The Place of Cybercrime - R. D. Sharapov (Сибирское юридическое обозрение, 2024)
This article addresses the criminal-legal characteristics of the location of cybercrimes – offenses committed using electronic or information and telecommunications networks, including the Internet. The concept of the crime’s location in criminal and criminal procedural law is examined, including possible approaches to defining a unified concept of location, which is associated with specific legal consequences in criminal and criminal procedural law: sector-specific (focused on issues within a specific field) and cross-sectoral (aiming for a universal definition applicable across fields). It is noted that all approaches require defining the crime’s location based on legal fiction. This means the crime’s location is formally tied to the territorial localization of one of the crime’s elements (usually the place of action and/or the place of social harm). Based on the explanations provided by the Plenum of the Supreme Court of the Russian Federation and current judicial practice, it is concluded that both criminal and procedural law regard the crime’s location as determined by the time of its commission (as per Article 9, Part 2, of the Criminal Code of the Russian Federation). Therefore, the location of a crime is considered to be where the socially dangerous action (or inaction) occurred, regardless of where the consequences took place. The article also analyzes issues surrounding the determination of cybercrime locations, considering the complex design of their objective aspects. The location of a single cybercrime involving several illegal actions, separated in both time and space, should be considered the location of each action. Procedurally, such a crime is regarded as “initiated in one place and completed in another”, which affects jurisdiction based on the “place of completion” (interpreted in procedural, rather than criminal, terms). This is typically the place where the final act that constitutes part of the crime occurred (per Article 32, Part 2, and Article 152, Part 2, of the Criminal Procedure Code of the Russian Federation).